Adding multiple micronutrient powders to a homestead food production programme yields marginally significant benefit on anaemia reduction among young children in Nepal. Issue 4 (December 2015) - Osei, Akoto K.; Pandey, Pooja; Spiro, David; Adhikari, Debendra; Haselow, Nancy; De Morais, Caroline; Davis, Dale
Abstract: Anaemia affects 46% of preschool‐aged children in Nepal. A cluster‐randomised study was conducted in rural Nepal to test whether providing micronutrient powders (MNP) in addition to enhanced homestead food production (EHFP) programme, consisting of home gardens, poultry and nutrition education, could lead to a higher reduction in anaemia compared with providing only EHFP. This sub‐study enrolled 335 children aged 6–9 months into one of three groups: (1) EHFP + MNP; (2) EHFP; or (3) control. The EHFP + MNP group received 60 sachets of MNP for flexible consumption at the start and 6 months later for a total supplementation period of 11 months. The MNP contained 15 micronutrients including iron (10 mg encapsulated ferrous fumarate). Haemoglobin and anthropometry were measured at baseline and post‐MNP supplementation. Mean ± SE haemoglobin concentration increased significantly in all groups, with a slightly higher but non‐significant increase in the EHFP + MNP and EHFP compared with control (difference‐in‐differences: 4.1 g L −1 for EHFP + MNP vs. control; 3.6 g L −1 for EHFP vs. control; 0.5 g L −1 for EHFP + MNP vs. EHFP). Anaemia decreased at a slightly higher magnitude in the EHFP + MNP [51.5 percentage points (PP)] than the EHFP (48.6 PP) and control (39.6 PP), with adjusted odds ratios (95% CI) at post‐supplementation of 0.52 (0.25–1.12) for EHFP + MNP and 0.69 (0.35–1.36) for EHFP, compared with control. There was no impact on child growth. Combining EHFP and MNP programmes yielded a marginally significant reduction in anaemia among children.